772 Examining sleep difficulties and suicide ideation among those reporting abuse and dependence on illicit drugs and alcohol. (3rd May 2021) - Robbins, Rebecca; DiClimente, Ralph J; Weaver, Matthew; Gangi, Catherine Di; Chalem, Isabel; Quan, Stuart; Klerman, Elizabeth
Abstract: Introduction: Sleep disturbance is associated with poor mental health and may contribute to initiating or continuing use/abuse of alcohol and drugs. Using data from a nationwide survey, we examined the relationship between sleep disturbance and suicide behaviors among youth and adults, including those who report drug/alcohol use and abuse. Methods: We analyzed data from the 2018 National Survey on Drug Use and Health (NSDUH), an annual survey collecting information about the use of illicit drugs and alcohol among non-institutionalized U.S. youth (age 12–17) and adults (age>17). The 2018 survey included 9, 398 youth and 43, 026 adult respondents. Depression was assessed in adults with the Kessler-6 and in youth with several questions assessing psychological distress. Those who scored at risk for psychological distress were also asked about sleep disturbance and suicidal behaviors (i.e., ideation, planning, attempt). All were asked to report their drug/alcohol use and/or abuse. Our study population included those who reported psychological distress. We conducted binary logistic regression to examine the relationship between suicidal behavior and sleep disturbance in this population. We also conducted sub-analyses to explore the relationship between suicidal behavior and sleep disturbance among those reporting drug/alcohol use and abuse. Results: Youth were 29% male and 71% female, adults were 36% male and 64% female. Adult participants, 39% were 18 to 25, 22% were 26 to 34, and 39% were age 35 and older. Among those with psychological distress, suicidal behavior was more likely among those who reported sleep disturbance (youth: OR=2.7, 95%CI:1.8–4.0; adults: OR=1.3, 95%CI:1.2–1.5). Also, among those with psychological distress, suicidal behavior was more likely among those who reported concomitant sleep disturbance and either alcohol abuse/alcoholism (youth: OR:3.3, 95%CI:1.6–7.0; adults: OR=1.4, 95%CI:1.1–1.7); illicit drug abuse (youth: OR=3.5, 95%CI:1.6–7.4; adults: OR=1.3, 95%CI:1.0–1.6); or alcohol and illicit drug abuse (youth: OR=3.2, 95%CI:1.5–6.9; adults: OR=1.4, 95%CI:1.1–1.7). Conclusion: Youth and adults with psychological distress and sleep disturbance are more likely to also report suicidal behaviors. Alcohol and drug use or abuse increase their risk for suicidal behavior compared to those who do not report sleep disturbance. Future work should include examination of causality and of interventions. Support (if any): NIH K24-HL105664, P01-AG009975, T32-HL007901, K01HL150339, 1R56HL151637